A new species of Microlicia and a checklist of Melastomataceae from the mountains of Capitólio municipality, Minas Gerais, Brazil - Romero, Rosana; Versiane, Ana Flávia Alves (Phytotaxa, 2014)
Microlicia furnensis, a new endemic species from campos rupestres of Capitólio municipality, Minas Gerais state, Brazil, is described and illustrated. The new species is characterized by its cream petals with pale pink blotches at the apex, sessile or subsessile leaves and golden glandular trichomes and short pale trichomes covering the leaves, pedicels, hypanthium and the calyx lobes. It resembles M. confertiflora, M. isophylla and M. flava, the latter also occuring in Capitólio, Minas Gerais state. A list of species of Melastomataceae from the mountains of Capitólio municipality is also provided.